Mechanisms of heat transfer for axisymmetric bubble impingement and rebound - MURRAY, DARINA; ROBINSON, ANTHONY; Donoghue, D.B.; Albadawi, A.; Delauré, Y.M.C. (My University, 2017)
Heat transfer enhancement resulting from the impingement and rebound of bubbles in confined geometries can play an important role in heat transfer applications. Limited studies exist on the impact behavior of large ellipsoidal bubbles against a horizontal surface, while the associated fluid flow field has received even less recognition. To address this, the current study investigates the dynamics of a single large ellipsoidal bubble impinging on a horizontal heated surface. The bouncing dynamics have been explored by utilizing synchronized high- speed and IR photography. Due to the large bubble size in the present study only a bubble with a low release to surface distance was found to have a symmetric bouncing event. The results showed that separated wake structures initially cooled the surface before the wake structures become counter productive and convect warm fluid onto the previously cooled surface. Two cooling zones were observed; the inner region due to the bubble and the outer region due to the bubble’s wake.
PUBLISHED
Keywords: Rising bubble; Bouncing bubble; Heat transfer enhancement; IR thermography; Smart & Sustainable Planet; HEAT TRANSFER ENHANCEMENT